1998
DOI: 10.1177/009102609802700406
|View full text |Cite
|
Sign up to set email alerts
|

Job Values in Today's Workforce: A Comparison of Public and Private Sector Employees

Abstract: Unlike workers in the ′70s and ′80s who valued interesting work above everything else, the results of this study suggest today's workers place the highest value on good wages and job security. A comparison of public and private sector workers revealed private sector workers place the highest value on good wages, while public sector workers valued interesting work the most. No significant difference was found between public and private sector employees in the importance placed on job security. These results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 0 publications
7
161
2
7
Order By: Relevance
“…On assessing data from the National Longitudinal Surveys of Youth (NLSY), DeSantis and Durst (1996) show that public employees report higher work satisfaction than private employees regarding organizational climate and quality of supervision. Karl and Sutton (1998) compared 170 public organizations with 47 private firms in the U.S. The results indicate that private sector workers value good wages the most, while public sector workers place higher value on significant and interesting work.…”
Section: Work Satisfaction On Public and Private Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On assessing data from the National Longitudinal Surveys of Youth (NLSY), DeSantis and Durst (1996) show that public employees report higher work satisfaction than private employees regarding organizational climate and quality of supervision. Karl and Sutton (1998) compared 170 public organizations with 47 private firms in the U.S. The results indicate that private sector workers value good wages the most, while public sector workers place higher value on significant and interesting work.…”
Section: Work Satisfaction On Public and Private Sectorsmentioning
confidence: 99%
“…For example, questions related to job security and social environment, public employees display higher levels of work satisfaction than private employees (DeTienne et al, 2012;Wang et al, 2012). However, when the questions are about compensation and the possibility of growth, private employees report significantly higher levels of work satisfaction (see also Rainey, 1983;Buelens and Broeck, 2007;Karl and Sutton, 1998).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…The second group of attributes relates to individual psychological factors. Many studies have found that some individuals are more attracted to and motivated to begin public service work (e.g., Perry and Wise 1990); public sector employees value non-monetary benefits more highly (e.g., Crewson 1997, Karl andSutton 1998), and public sector jobs are especially attractive to risk-averse individuals 1 Using data for German males, Dustmann and van Soest (1998) found that the positive effect of education on public sector employment choice disappears after controlling education with family background variables. Based on this finding, they conclude that the positive relationship found in standard models is not structural but rather reflects unobserved heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Uit onderzoek blijkt dat loopbaanontwikkelingsmogelijkheden belangrijk worden geacht door ambtenaren voor hun ontwikkeling van trots (Vermeeren & Van Geest, 2012: 323 (Karl & Sutton, 1998;Perry & Wise, 1990;Rainey, 1982 Voor hypothese zes -aard van het werk -zijn alle respondenten op basis van hun antwoorden ingedeeld in de groep overwegend uitvoerende ambtenaren dan wel overwegend beleidsvoorbereidende/beleidsmakende ambtenaren (zie de appendix voor verdere uitleg). Voor het toetsen van de variabele behorende bij hypothese zeven -relatie met collega's -zijn de antwoorden op de bijbehorende stelling gedichotomiseerd naar (helemaal) oneens en (zeer) mee eens.…”
Section: Cursussenunclassified